2021
DOI: 10.17485/ijst/v14i22.736
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Mechanical Behaviour of Micro B4C Particles Reinforced Al6061 Alloy Metal Composites

Abstract: Objective: To develop and evaluate the mechanical behavior of 3, 6, 9 and 12 wt. % of B 4 C reinforced Al6061 alloy composites. Method: These composites were produced by utilizing stir cast process. The prepared metal composites were characterized by SEM, EDS and XRD analysis to know the distribution of particles as well as presence of particles in the Al6061 alloy. Various mechanical properties were evaluated as per ASTM standards to know the impact of boron carbide particles on the properties of metal compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…% of B 4 C composites. The SEM micrographs obviously showed the solid interfacial holding of Al2030 network and B 4 C; this holding assists with moving the pivotal elastic load from grid to the B 4 C (12) . This hard molecule keeps away from the plastic progression of Al grid and subsequently upgrades the load carrying limit of Al2030 matrix.…”
Section: Ultimate Tensile and Yield Strengthmentioning
confidence: 88%
“…% of B 4 C composites. The SEM micrographs obviously showed the solid interfacial holding of Al2030 network and B 4 C; this holding assists with moving the pivotal elastic load from grid to the B 4 C (12) . This hard molecule keeps away from the plastic progression of Al grid and subsequently upgrades the load carrying limit of Al2030 matrix.…”
Section: Ultimate Tensile and Yield Strengthmentioning
confidence: 88%
“…The first is the reinforcing phase, and the second is the matrix phase, which is typically an alloy of metals. The enhanced qualities of composites and the material properties that cannot be achieved by a single phase are both enhanced by combining the two phases [ 23,24]. In an effort to create MMCs with exceptional strength, researchers are devoting more time and energy to reinforcing development.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the wear and friction being system dependent phenomenon were found to be influenced by parameters like reinforcement, method of processing composite, different phases in microstructure, stress level, relative speeds, contact condition and system generated in situ tribolayer. Kumar et al (20) Chartersied physical, mechanical and tribological response of Al 6061 composite with particulated nano sized ZrO 2. The wear results showed that addition of nano sized ZrO 2 particles improved wear response.…”
Section: Introductionmentioning
confidence: 99%